Etiology and Related Factors of Postoperative Delirium in Orthopedic Surgery - Song, Kyung-Jin (Clin Orthop Surg, 2019)
BACKGROUND: Delirium is a serious complication for elderly patients after orthopedic surgery. The purpose of this study was to assess the etiology and related factors of delirium after orthopedic surgery in Korea. METHODS: We retrospectively reviewed the medical records of 3,611 patients over 50 years who had orthopedic surgery. The age of patients (50s, 60s, 70s, and > 80s), type of anesthesia (general, spinal, and local), operation time (more than 2 hours vs. less than 2 hours), surgical site (spine, hip, knee, or others), and etiology (trauma or disease) were compared to determine possible risk factors of delirium after orthopedic surgery. RESULTS: Of 3,611 patients, 172 (4.76%) were diagnosed with delirium after orthopedic surgery. Postoperative delirium occurred in 1.18% in their 50s, 3.86% in their 60s, 8.49% in their 70s, and 13.04% in > 80s (p < 0.001). According to anesthesia type, 6.50% of postoperative delirium occurred after general anesthesia, 0.77% after spinal anesthesia, and 0.47% after local anesthesia (p < 0.001). More than 2 hours of operation was associated with higher occurrence of delirium than less than 2 hours was (5.88% vs. 4.13%, p = 0.017). For the etiology, 8.17% were trauma cases and 3.02% were disease (p < 0.001). Postoperative delirium occurred in 22 of 493 patients (4.46%) after spine surgery, 18 of 355 patients (5.07%) after hip surgery, 17 of 394 patients (4.31%) after knee surgery, and 15 of 1,145 patients (1.31%) after surgery at other sites (p < 0.001). CONCLUSIONS: Postoperative delirium was more common in older patients who had surgery under general anesthesia, whose surgery took more than 2 hours, and who were hospitalized through the emergency room.